Interpretation of Levinas in Marco Maria Olivetti’s Philosophy - Šerpytytė, Rita (Religija ir kultūra, 2024)
This article analyses the original interpretation of Emmanuel Levinas’s philosophy by one of the most prominent Italian philosophers of the 20th century, Marco Maria Olivetti. It shows that the key point that Olivetti ascribes to Levinas’s philosophical position is Levinas’s notion of subjectivity. The article analyses how Olivetti’s exploration of Levinas’s notion of the subject anticipates the challenges that only twenty-first-century philosophy has accepted. It shows that the basis of Olivetti’s insightful and original interpretation of Levinas lies in a certain transition of Levinas’s philosophy to a different level than that envisaged by Western modern thought. For Olivetti, it is particularly important to stress that the Levinasian different subject presented in Autrement qu’être is described as “not a logical but an ethical subject”, which implies a passage to another level, a transcending, a transcendence. But it is not only the transcendence of the logical level that we are dealing with. Rather, this transcendence of the formal logical level, which occurs not only in Autrement qu’être but already in Totalité et infini, becomes a challenge to the logical level, namely in discourse. The article shows how the Levinasian notion of the subject correlates with the contemporary interpretation of subjectivity, since the ego is thought to be the one who says “ego”.
Keywords: Levinas; Marco Maria Olivetti; subject; ego; a transcendental; language